Kebijakan Manajemen Program Pembinaan Atlet Olahraga Panahan Komite Olahraga Nasional (KONI) Jambi - David Iqroni; Muhammad Ali (Universitas Batanghari Jambi, 2022)
Management has a broad meaning. There are many definitions of management theoretically. For example, according to Terry (2008), management is a process consisting of actions that include planning, organizing, driving, and controlling carried out to determine and achieve the goals set using human resources and other sources. This research is expected to provide benefits both theoretically and practically. Theoretically, this research is expected to contribute to further scientific development, especially those related to management in an organization to produce or improve achievement. The positive results from this research can be used as a guide in carrying out the development of athlete achievement in Jambi Province, especially for archery sports. Practically, the results of this study are expected to be input for policymakers and other stakeholders with interest in the management policy of the archery athlete coaching program, especially KONI and archery branch administrators regarding the management system used in Jambi Province, and as consideration for local government in fostering sports organizations and other public organizations.